(untitled) (International relations and international law Journal, 2016)
The article deals with questions of «Culture of speech», «Language norm as the basis of culture of speech». The article describes aspects of culture of speech: normative, communicative, ethic. Communicative qualities of speech, basic units and types of communication, modern communicative code – specifics of Kazakh speech etiquette – are analyzed. Communicative expediency is considered one of the main categories of theory of culture of speech, it is therefore important to know basic communicative speech qualities that render the best effect on the addressee taking into account a certain situation and in accordance with the put aims and tasks. Exactness, clearness, riches and variety of speech, her cleanness, expressiveness behave to them. The degree of knowledge of speech etiquette determines the degree of professional fitness of man. The knowledge of speech etiquette assists acquisition of authority, generates trust and respect. Knowledge of rules of speech etiquette, their observance, allows to the man to feel confidently. Conclusions are drawn about the necessity of introduction of elective course of «Сulture of speech in the national language» for the students of faculty of international relations.